A stand-alone cobalt bis(dicarbollide) photoredox catalyst epoxidates alkenes in water at extremely low catalyst load. Issue 24 (29th November 2021) - Guerrero, Isabel; Viñas, Clara; Romero, Isabel; Teixidor, Francesc
Abstract : Cobaltabis(dicarbollide), Na[3, 3′-Co(η5-1, 2-C2B9H11)2] Na[1] ), is an efficient photoredox catalyst for the epoxidation of alkenes in water, at low catalyst loading and requiring short reaction times (15–30 min). Abstract : The cobalt bis(dicarbollide) complex, Na[3, 3′-Co(η 5 -1, 2-C2 B9 H11 ) (Na[1] ), is an effective photoredox catalyst for the oxidation of alkenes to epoxides in water. Advantageous features of Na[1] include its lack of photoluminescence, high solubility and surfactant behavior in aqueous media, as well as the donor ability of the carborane ligand and high oxidizing power of the Co 4+/3+ couple. These features differentiate it from the well-known and widely used photosensitizer tris (2, 2′-bipyridine) ruthenium(ii ) ([Ru(bpy)3 ] 2+ ), which also participates in electron transfer through an outer sphere mechanism. A comparison of the catalytic performance of [Ru(bpy)3 ] 2+ with Na[1] for alkene photo-oxidation is fully in favor of Na[1], as the former shows very low or null efficiency. With a catalyst loading of 0.1 mol% conversions between 65–97% have been obtained in short reaction times, 15 minutes, with moderate selectivity for the corresponding epoxide, due to the formation of side products as diols. But when the catalyst loading is reduced to 0.01 mol%, the selectivity for the corresponding epoxide increased considerably, being the only compound formed after 15 minutes of reaction (selectivity >99%). High TON values have been obtained (TON = 8500) for the epoxidation of aromatic and aliphatic alkenes in water. We have verified that Na[3, 3′-Co(η 5 -1, 2-C2 B9 H11 )2 ] acts as a photocatalyst in both the epoxidation of alkenes and in their hydroxylation in aqueous medium with a higher rate for epoxidation than for hydroxylation. Preliminary photooxidation tests using methyl oleate as the substrate led to the selective epoxidation of the double bond. These results represent a promising starting point for the development of practical methods for the processing of unsaturated fatty acids, such as the valorisation of animal fat waste using this sustainable photoredox catalyst.